A INFLUÊNCIA DAS PRÁTICAS PEDAGÓGICAS DOCENTES E DAS BARREIRAS DISCENTES SOBRE O DESENVOLVIMENTO DA CRIATIVIDADE DO FUTURO ADMINISTRADOR - FABRETE, TERESA CRISTINA LOPES (2015)
The companies which crave ensure and improve their position within an increasingly competitive market, need to be always updated and in constant evolution. In their continuous pursuit for evolution, they invest in Research & Development (R&D) projects and in its human capital to promote creativity and organizational innovation. People have a fundamental role in the development of innovation, but for it to flourish constantly it’s needed commitment and creativity to generate ideas. Creativity is to think the new; innovation is making things happen. However, find people with these qualities is not always an easy task and it is often necessary to encourage these skills and characteristics, in them, in order to become effectively creative. The graduation programs, can be an important tool for development of these aspects, characteristics and abilities, using teaching methods and practices that will assist in the development of creativity, because the teaching-learning environment is important in people’s development. The objective of this study is to identify which factors have the greater push, on the creativity’s development, in an undergraduate administration program, analyzing the influence of teachers’ pedagogical practices and the student’s internal barriers. The theoretical framework is main based on the work of Alencar, Fleith, Torrance and Wechsler. A cross-sectional survey This study has a quantitative approach, using as target audience the students of a management university course in São Paulo, whom has answered 465 compounds questionnaires we’ve used three questionnaires scales. For teaching practices was adapted from Educational Practice in relation to Creativity. For internal barriers was adapted scale of Personal Creativity Barriers. For the analysis of the perception of creativity development was adapted, built and checked a scale based on the framework of characteristics of a creative person. The descriptive and exploratory factorial statistical analyzes were performed using the Statistical Package for software Social Sciences (SPSS), while the factor confirmatory analysis to the context under study for measurement of the influence of pedagogical practices and internal barriers on the factors influencing the perception of creativity development were performed with analysis by structural equation modeling using the algorithm Partial Least Squares (PLS), the Smart PLS 2.0 software. The results showed the pedagogical practices and the internal barriers of the students explain 40% of the creative development of perception, and the pedagogical practices that most influence. The survey also pointed out that the type of issue and period in which the student is enrolled have no influence on any of the three constructs, only the teacher influences the pedagogical practices.